Ucast EDRF-NO v regulacích kostního průtoku krve u potkanů: inhibice s L-NAME - Kapitola, J; Andrle, J; Haas, T; Kubícková, J (Sbornik lekarsky, 1996)
EDRF-NO probably participates-besides the prostaglandins [3, 4]-in local circulatory changes in the bones of female rats with modified level of sex hormones; we could demonstrate it indirectly using methylene blue as a blocking agent [5]. In this paper, we present corresponding results of two experiments with NG-nitro-arginine methyl ester (L-NAME) as a substance blocking the production of endothelium derived relaxing factor, i.e. nitric oxide (EDRF-NO). Circulatory values were estimated by means of 85Sr-microspheres. In experiment A we ascertained whether the duration of L-NAME administration (0.025% in the food) influenced the effect. It could be demonstrated that the effect of one week's, two weeks', or four weeks' administration of L-NAME was the same: 85Sr-microsphere uptake and blood flow throught the tibia of female rats, increased after oophorectomy (OOX, performed four weeks prior to the experiment), was significantly suppressed to the level in sham-operated animals. In the experiment B, L-NAME was administered in the food in concentration of 0.05% for two weeks prior to the experiment. 85Sr-microsphere uptake was decreased significantly after L-NAME in the tibia of sham-operated females, in the tibia and distal femur of OOX animals; no significant changes were found in the diaphysis of femur and in calvaria. Blood flow values were significantly decreased in all bone samples of OOX females and in tibia of sham-operated rats (besides the local reaction also due to the decrease in the cardiac output). In both experiments the cardiac output was decreased and blood pressure elevated after L-NAME. It can be concluded, from the results of both experiments, that the blockade of EDRF-NO production by L-NAME decreases local circulatory values in the bones of female rats-particularly OOX-in a similar way as methylene blue; however, in contrast to methylene blue, L-NAME induces marked increase in the blood pressure and partially decrease in the cardiac output. Thus, as in the case of methylene blue, the effect of L-NAME on the circulation of blood in the rat bones supports the hypothesis of the participation of EDRF-NO in bone blood flow regulations.
Keywords: Nitric Oxide; regionální krevní průtok; Ovariectomy; kosti a kostní tkáň; Strontium Radioisotopes; Femur; Regional Blood Flow; radioizotopy stroncia; oxid dusnatý; Tibia; methylenová modř; rychlost toku krve; NG-Nitroarginine Methyl Ester; Hemodynamics; krysa rodu Rattus; Animals; ženské pohlaví; ovarektomie; zvířata; Rats; Methylene Blue; femur; NG-nitroargininmethylester; hemodynamika; Female; Bone and Bones; Blood Flow Velocity; tibie